Strategic Financial Planning and Its Effect on Company Resilience in an Uncertain Market in Indonesia - Judijanto, Loso; SY, Arniwita; Ermaini, Ermaini (West Science Business and Management, 2025)
This study examines the effect of strategic financial planning on company resilience in an uncertain market environment in Indonesia. Using a quantitative approach, data were collected from 55 companies through a structured questionnaire. Strategic financial planning was assessed through budgeting, forecasting, risk management, and resource allocation, while company resilience was measured by adaptability, sustainability, and financial stability. Data analysis was conducted using SPSS version 25, incorporating descriptive statistics, correlation analysis, and regression analysis. The results indicate a strong positive relationship (r=0.72,p
Keywords: Strategic Financial Planning; Company Resilience; Uncertain Market; Risk Management; Indonesia